Congestive heart failure model representing aortic banding induced hypertrophy: A study to analyse extent of pressure overload and alteration in myocardial structure and function. (June 2021) - Patel, Arti; Patel, Darshna
Abstract: Congestive Heart failure (CHF) is a severe pathology representing a major public health problem in industrialized nations which is increasing in prevalence and incidence. The aortic banding rat model provides steady progression of cardiac dysfunction under chronic pressure overload. Present study evaluated two abdominal aortic constriction techniques including constriction of aorta above renal arteries and between renal arteries. The extent of constriction was varied with 22 G and 24 G needles and the duration for evaluation of CHF was also varied by terminating the banded animals after 6 and 8 weeks of banding. Various hemodynamic, ECG and tissue parameters were evaluated after banding to see the progression of CHF. The findings revealed that the constriction of the aorta above both renal arteries with 24 G needle is a better technique amongst other tested banding techniques as the rate of progression of CHF was found to be maximum with it. On the basis of above study, it was concluded that, aortic banding above both renal arteries with 24 G needle is a better technique for induction of pressure overload and for further observation in transition of the cardiac compensatory to decompensatory phase, the duration of the model needs to be prolonged.